Dispute Settlement Mechanisms under the ASEAN Legal Framework - Jayadi, Anbar (UI Scholars Hub, 2016)
ASEAN has great ambitions. One (or two, even three and more) of them was laid out in ASEAN Economic Blueprint. It is to make ASEAN achieves higher levels of economic dynamism, sustained prosperity, inclusive growth and integrated development,1 visionary indeed. Nonetheless, it is necessary to always think and prepare if disputes happen. How to both face and to the extent, solve a dispute will determine whether ASEAN member states are committed to ASEAN and its ambitions as an intergovernmental organization.2 This book, as a matter of fact, do point out the necessity to examine existing dispute settlement mechanisms and discuss about it comprehensively by pulling out red line from the ASEAN Charter, the 2010 ASEAN Charter’s Protocol on Dispute Settlement Mechanism to the ASEAN Comprehensive Investment Agreement.